(untitled) (SOMTU Journal of Business and Management Research, 2025)
This research aims to understand the impact of green marketing factors on green purchase intention and purchase behavior, particularly examining how green product quality, green value, and perceived consumer effectiveness influence purchase intentions and consumption behavior in Kathmandu Metropolitan City. In this study, causal research is used, and data is gathered from 287 consumers through convenience sampling via Google Forms. A 7-point Likert scale was applied, and the data were analyzed using Smart PLS with Structural Equation Modeling. Findings show that green purchase intention, green value, and perceived consumer effectiveness have a positive and significant impact on green consumption behavior. Similarly, green product quality, green value, and perceived consumer effectiveness significantly influence green purchase intention. However, there is a positive but not significant relationship between green product quality and green consumption behavior. Results further show that green purchase intention fully mediates the relationship between green product quality and green consumption behavior but partially mediates the relationship between green value and perceived consumer effectiveness with green consumption behavior. It concludes with the importance of aligning green marketing strategies with consumer values and self-efficacy, while policymakers should invest in education and awareness to foster consumer belief in the effectiveness of individual action.